Hidroxiapatita sintética associada ou não à fração total de células mononucleares na regeneração de osso alveolar de cães - Fontes, Erica Batista (2009)
Several factors, including periodontal disease, can lead to alveolar bone reabsorbtion. The aim of this study was to investigate and compare the efficiency of mononuclear bone marrow cells (MN-BMC) associated with hydroxiapatite with hydroxiapatite alone, to promote bone regeneration. The dogs were separated in two groups (GI and GII) of nine animals. A defect of 4,3 mm diameter was surgically induced by a trephine bur between the dental roots of the fourth pre-molar tooth. In each dog the wound was treated with FMCB associated with HA (GII) or HA alone (GI). Bone marrow was extracted from all four members, the surgical access for this procedure consisted in the major tracanter of the femur and humerus condyle. In order to process the bone marrow a Histopaque® 1.077 gradient was used to separate the layer of mononuclear cells. A small sample of this layer was used for verification of total cell count and viability. The obtained mononuclear cells were then transplanted to the patients as soon as possible. Clinical evaluations for 7 days, radiologic examinations at 14, 45 and 60 days, and histological analyzes at 14, 45 and 60 days were made in order to investigate and compare the efficiency of the treatments in bone regeneration and/or reparation. The surgical procedure was adequate for the investigation purpose and the trephine bur permitted standardization of the bone defects. Adequate cell number and viability were obtained from the four bone marrow extractions followed by their processing. Scarring of the surgical wound was satisfactory and occurred similarly for the two groups. Both groups presented similar progress by radiological examination. Immediate postsurgical exams indicated that the bone defect had an adequate fulfillment. At 14 days, radiopacity had diminished when compared with immediate post-surgical finding; this was followed by an increase in radiopacity at 45 days, in both groups. Even though bone defect was still visible, radiopacity at 60 days was higher than that of 45 days. Histological evaluation indicated a progressive bone formation process in both groups. Immature bone was already visualized at 14 days in GII. In fact, histological and statistical analyzes provide reliable data that bone regeneration occurred in a less amount of time in GII at a probability of 5%. HA was still present at the 60 day group evaluation witch indicates that this biomaterial had not been completely absorbed at this time. Additionally, foreign body reactions were not present proving that the bone grafts used was biocompatible. In summary, this study has shown that the use of MN-BMC in combination with HA resulted in improvement in bone reparation when compared with HA alone.